Making Sense of an Elusive Concept: Academics' Perspectives of Quality in Higher Education - Lazarus Nabaho; Jessica Norah Aguti; Joseph Oonyu (Laureate Education Inc, 2017)
Objective: Since the 1990s studies on how stakeholders in higher education perceive quality have burgeoned. Nevertheless, the majority of studies on perception of quality in higher education focus on students and employers. The few studies on academics' perceptions of quality in higher education treat academics as a homogeneous group and, therefore, do not point out cross-disciplinary perspectives in perceptions of quality. This article explores how academics across six disciplines perceive quality in higher education. Method: The article is anchored in the interpretivist paradigm. Data was collected from 14 purposely selected academics at Makerere University in Uganda and analyzed using thematic analysis. Results: The findings show that academics perceive quality in higher education as transformation, fitness for purpose, and exceptional. The findings further demonstrate that a stakeholder group or an individual stakeholder can subscribe to a notion of quality in higher education but voice divergent views on its variants. Similarly, the academic discipline, the perceived purpose of higher education, and the problems within a higher education system have an influence on stakeholders' conception of quality in higher education. Conclusions: From the findings it can be inferred that quality in higher education defies a single definition and that stakeholders' perceptions of quality do not take place in a vacuum. Implication for Theory and/or Practice: The multidimensional nature of quality and the contestations around it necessitate a multidimensional approach to assuring and assessing it.